Pengembangan E-Modul IPS Berbantuan Al-Qur’an untuk Pembelajaran Mendalam Berbasis Book Creator di SMP: Development of a Quran-Integrated Social Studies E-Module for Deep Learning Using Book Creator in Junior High Schools - Siti Munira; Sumanti Sumanti; Hariki Fitrah (ITScience (Information Technology and Science), 2026)
This study aimed to develop an Islamic-values-based Social Studies (IPS) E-Module assisted by the Qur’an using Book Creator and to examine its feasibility and effectiveness in Social Studies learning at the junior high school level. This study employed a Research and Development (R&D) method using the DDD-E (Decide, Design, Development, Evaluate) model developed by Ivers and Barron (2002). The research subjects consisted of 32 eighth-grade students at UPTD SMP Negeri 1 Juli. Data were collected through expert validation questionnaires, student and teacher response questionnaires, and learning achievement tests. The data were analyzed using descriptive statistics and empirical testing to determine improvements in students’ learning abilities. The results showed that the Qur’an-assisted Social Studies E-Module obtained a very good category based on evaluations by the material expert (88%), media expert (100%), learning strategy expert (98%), language expert (98%), and IT expert (92.5%). Students’ responses to the use of the E-Module reached 94%, categorized as very good, while the Social Studies teacher’s response reached 97%, with an average score of 4.775. Furthermore, the empirical test results indicated a significant improvement in students’ learning abilities, as demonstrated by higher posttest scores compared with pretest scores (p < 0.05). Based on these findings, the Qur’an-assisted Social Studies E-Module developed using Book Creator is considered feasible and effective for use in Social Studies learning at the junior high school level. The E-Module can support meaningful and interactive learning while integrating Qur’anic values into the Social Studies learning process.